2017
DOI: 10.4174/astr.2017.92.6.396
|View full text |Cite|
|
Sign up to set email alerts
|

Effectiveness of thymoquinone, zeolite, and platelet-rich plasma in model of corrosive oesophagitis induced in rats

Abstract: PurposeThe effectiveness of platelet-rich plasma (PRP), thymoquinone, and zeolite in corrosive esophageal burns was investigated in a rat model.MethodsFour groups were comprised as containing 10 rats in each group. For group I, oesophagitis was induced and no other procedure was performed (control group). For group II, oesophagitis was induced and thymoquinone was administered for 1 week via oral gavage once a day (thymoquinone group). For group III, oesophagitis was induced for 1 week via oral gavage once a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…On the contrary, TQ lowered the plasma levels of E-selectin, CRP, and IL-6. This result agreed with Karaca et al [ 33 ], who noticed a significant reduction in interleukin-1 beta (IL-1 β ), IL-6, tumor necrosis factor-alpha (TNF- α ), and monocyte chemoattractant protein-1 (MCP-1) in rats subjected to experimental induction of esophagitis. Also, it was found that TQ has a role against inflammatory progression in the hippocampal tissues due to lipopolysaccharide-induced inflammation in rats [ 34 ].…”
Section: Discussionsupporting
confidence: 92%
“…On the contrary, TQ lowered the plasma levels of E-selectin, CRP, and IL-6. This result agreed with Karaca et al [ 33 ], who noticed a significant reduction in interleukin-1 beta (IL-1 β ), IL-6, tumor necrosis factor-alpha (TNF- α ), and monocyte chemoattractant protein-1 (MCP-1) in rats subjected to experimental induction of esophagitis. Also, it was found that TQ has a role against inflammatory progression in the hippocampal tissues due to lipopolysaccharide-induced inflammation in rats [ 34 ].…”
Section: Discussionsupporting
confidence: 92%
“…ARP is an inducible inflammation. Macroscopical, histopathological, and immunohistochemical analyses have been performed to determine this inflammation [ 15 16 17 18 19 20 21 22 ]. In this study, to show the inflammation, markers of IL-1β, TNF-α, and HIF1α cytokines were investigated; to show fibrosis in the rectal tissue, FGF2 was used as a marker and VEGF marker was used to show angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it activates the vascular endothelial cells [ 19 ]. TNF has an effect of oxidative damage on endothelial cells and increases the number of adhesion molecules; it also induces angiogenesis and arranges hematopoiesis [ 20 ]. Moreover, angiogenesis and endothelial cell proliferation can also be induced by FGF or VEGF [ 21 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…TQ and PRP composites with zeolite showed positive outputs on recovery in esophagitis by lessoning inflammation in the contacted area. 109 Moreover, proper oxygen supply to cells is a challenging issue in tissue engineering scaffolds. Ninan et al fabricate scaffold based on gelatin/copper‐faujasites (CAF) as a wound dressing.…”
Section: Zeolite In Tissue Engineering and Regenerative Medicinementioning
confidence: 99%